What Happens to the Careers of European Workers when Immigrants "Take their Jobs"? - Cristina Cattaneo; Carlo V. Fiorio; Giovanni Peri (Fondazione Eni Enrico Mattei (FEEM), 2014)
Following a representative longitudinal sample of native European residents, over the period 1995-2001, we identify the effect of the inflows of immigrants on their career, employment and wages. We use the 1991 distribution of immigrants by nationality across European labor markets to construct an imputed inflow of the foreign-born population that is exogenous to local demand shocks. We also control for .fixed effects that absorb individual, country-year, occupation group-year and occupation group-country heterogeneity and shocks. We find that native European workers are more likely to move to occupations associated with higher skills and status when a larger number of immigrants enter their labor market. As a consequence of this upward mobility their wage income also increases with a 1-2 years lag. We find no evidence of an increase in their probability of becoming unemployed.
Keywords: J61; O15; 330; Immigrants; Job Upgrading; Mobility; Self-employment; Europe